The Influence of Financial Management, Business Capital, Business Income, Product Innovation and Marketing Strategy on the Success of Micro Businesses in the Culinary Sector in Bima City - Khas Sukma Mulya; Amanda (CV Edujavare Publishing, 2026)
Culinary micro-enterprises play a significant role in the regional economy, including in Bima City. However, their success is still influenced by various factors, the results of which are inconsistent across regions. This study aims to analyze the influence of financial management, business capital, business income, product innovation, and marketing strategies on the success of culinary micro-enterprises in Bima City, both partially and simultaneously. This study uses a quantitative approach with a survey design of culinary micro-enterprises in Bima City, using a Likert-scale questionnaire instrument analyzed through multiple linear regression with the help of SPSS.The results showed that all five variables simultaneously had a significant effect on business success. Partially, financial management, business capital, and business income had a significant positive effect, while product innovation and marketing strategy were insignificant. The R² value of 0.495 indicates that 49.5% of the variation in success was explained by the research variables.